W CZECHACH BEZ ECHA? TŁUMACZENIA LITERATURY POLSKIEJ NA JĘZYK CZESKI W XXI WIEKU - Jeništa, Jan (Prace Polonistyczne, 2020)
The article surveys the last twenty years of the presence of Polish literature in the Czech Republic. The study focuses on the types and genres of literary texts translated into Czech, the total number of translations published in the period under discussion, as well as typical publishing practices and the network of support offered by Polish cultural institutions. Furthermore, the article offers some insight into the publishing industry and book market in the Czech Republic. The author examines the position of translators from Polish in this industry and the extent of their influence on what is published and how. The quantitative analysis presented in the article sheds light on certain prevalent trends, such as the rising popularity of Polish non-fiction books and the unique status of Polish fantasy literature. Investigating these trends further, the author aims to answer the question of whether the relatively high number of books translated from Polish and currently available on the Czech market is indicative of an actual rise of general interest in Polish literature.